9. Solve 3x + 2b = 6c for x.

Step 1: 3x + 2b - 2b = 6c - 2b subtract 2b from both sides

Step 2: 3x = 6c - 2b combine like terms/simplify

Step 3: (3x)/3 = (6c)/3 - 2b divide by 3 on both sides to get x isolated Step 4: x = 2c - 2b simplify/final answer

Which statement is TRUE?

(1 point)

The process has an error. The correct answer is x = (4kc)/3

The process has an error. The correct answer is x = 2c - 2/2 * b

The process is correct.

The process has an error. The correct answer is x = - 48 - c

1 answer

The correct answer is: The process is correct.
Similar Questions
  1. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
  2. Consider the sequence of steps to solve the equation:5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 5 answers
  3. Fill in the spaces to solve each step of the problem 14(x+3)=5.(2 points)Step 1: ( )14(x+3)=5( ). Step 2: x+3= Step 3: Subtract
    1. answers icon 1 answer
  4. Fill in the spaces to solve each step of the problem 14(x+3)=5 .(2 points)Step 1: (?)14(x+3)=5(?). Step 2: x+3= ? .Step 3:
    1. answers icon 1 answer
more similar questions